Proceedings of the 1st International Conference on Lifelong Learning and Education for Sustainability (ICLLES 2019) 2020
DOI: 10.2991/assehr.k.200217.020
|View full text |Cite
|
Sign up to set email alerts
|

Higher Intermediate Students’ Discourse Competence in Presenting Final Project

Abstract: This research aims at describing the discourse competence as part of communicative competence of higher intermediate students in delivering final project presentation. Higher intermediate level was chosen as the subject of the research because it is the highest level in learning English for high school students at an English course in Bukittinggi City. Qualitative descriptive method was used in conducting this research. The subjects were eleven students of higher intermediate class of the English course in Buk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The findings revealed that students lack knowledge of the appropriate use of markers when performing oral presentations. Elza (2020) analyzed the oral presentations of school students. The focus of research was on the students" discourse competence in conducting final project presentation.…”
Section: Review Of Past Studiesmentioning
confidence: 99%
“…The findings revealed that students lack knowledge of the appropriate use of markers when performing oral presentations. Elza (2020) analyzed the oral presentations of school students. The focus of research was on the students" discourse competence in conducting final project presentation.…”
Section: Review Of Past Studiesmentioning
confidence: 99%